Some inequalities of the Turán type for confluent hypergeometric functions of the second kind - QI, Feng (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
In the paper, by virtue of the H¨older integral inequality, the authors derive some inequalities of the Turán type for confluent hypergeometric functions of the second kind, for the Mellin transforms, and for the Laplace transforms, and improve some known inequalities of the Turán type. Mathematics Subject Classification (2010): 26D15, 26D20, 26D99, 33C15, 44A10, 44A15.